Modification of a Solar Thermal Collector to Promote Heat Transfer inside an Evacuated Tube Solar Thermal Absorber - Rasa Supankanok; Sukanpirom Sriwong; Phisan Ponpo; Wei Wu; Walairat Chandra-ambhorn; Amata Anantpinijwatna (My University, 2021)
Evacuated-tube solar collector (ETSC) is developed to achieve high heating medium temperature. Heat transfer fluid contained inside a copper heat pipe directly affects the heating medium temperature. A 10 mol% of ethylene-glycol in water is the heat transfer fluid in this system. The purpose of this study is to modify inner structure of the evacuated tube for promoting heat transfer through aluminum fin to the copper heat pipe by inserting stainless-steel scrubbers in the evacuated tube to increase heat conduction surface area. The experiment is set up to measure the temperature of heat transfer fluid at a heat pipe tip which is a heat exchange area between heat transfer fluid and heating medium. The vapor/ liquid equilibrium (VLE) theory is applied to investigate phase change behavior of the heat transfer fluid. Mathematical model validated with 6 experimental results is set up to investigate the performance of ETSC system and evaluate the feasibility of applying the modified ETSC in small-scale industries. The results indicate that the average temperature of heat transfer fluid in a modified tube increased to 160.32 °C which is higher than a standard tube by approximately 22 °C leading to the increase in its efficiency by 34.96%.
Keywords: Working fluid; Solar Thermal and Photovoltaic Systems